Plan de inversión para la creación de un patio logístico en Buenaventura Valle del Cauca (2013)
Due to port development that comes about to Buenaventura courtyards requirements for port logistics warehousing services, packing and unpacking, are developed in parallel with port activities and undergo an exponential growth in demand. Because of this is to determine the feasibility of creating a patio that offers logistics warehousing services, packing and unpacking in the city of Buenaventura - Antioquia. This requires performing a study to identify the market, identify technical requirements, determine the organizational and legal requirements, financial analysis to determine the feasibility. Once developed the studies found that Bonaventure leads the maritime foreign trade activity in Colombia, the existing infrastructure allows you to have two ports, one still in the process of modernization and other large mega projects. FTA with Canada, European Union and United States. The technical aspects is not a problem at the level of fixed asset requirements and knowledge on the topic of port logistics, administrative requirements compendium of rules and laws necessary to comply fully with the legal part of this type of company, the aspect showed business investment company makes this idea a viable alternative: the net present value, internal rate of return and benefit cost ratio concluded that the investment is viable within five years projected.